Regulation of senescence traits by MAPKs - Anerillas, Carlos; Abdelmohsen, Kotb; Gorospe, Myriam (GeroScience, 2020)
A phenotype of indefinite growth arrest acquired in response to sublethal damage, cellular senescence affects normal aging and age-related disease. Mitogen-activated protein kinases (MAPKs) are capable of sensing changes in cellular conditions, and in turn elicit adaptive responses including cell senescence. MAPKs modulate the levels and function of many proteins, including proinflammatory factors and factors in the p21/p53 and p16/RB pathways, the main senescence-regulatory axes. Through these actions, MAPKs implement key traits of senescence—growth arrest, cell survival, and the senescence-associated secretory phenotype (SASP). In this review, we summarize and discuss our current knowledge of the impact of MAPKs in senescence. In addition, given that eliminating or suppressing senescent cells can improve health span, we discuss the function and possible exploitation of MAPKs in the elimination (senolysis) or suppression (senostasis) of senescent cells.